2010
DOI: 10.1016/j.otohns.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in adolescents with prelinguistic deafness

Abstract: CI was shown to be a useful device with the ability to reverse the adverse consequences of hearing loss, particularly for prelingual adolescents who receive implantation early in life and who present a hearing threshold of 100 dB or better both at diagnosis and at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Subjects whose scores remained below 30% in the open-set word recognition test are labeled "poor performers" and marked with an asterisk in both Tables 1 and 2. The 30% criterion applied was the same as that by Arisi et al [2010] and Caposecco et al [2012]. If the difference score of an individual subject in Table 2 was ≤5%/≤5 wpm, the result was considered to be stable (no change).…”
Section: Study Objective 1: Changes In Auditory Performancementioning
confidence: 99%
“…Subjects whose scores remained below 30% in the open-set word recognition test are labeled "poor performers" and marked with an asterisk in both Tables 1 and 2. The 30% criterion applied was the same as that by Arisi et al [2010] and Caposecco et al [2012]. If the difference score of an individual subject in Table 2 was ≤5%/≤5 wpm, the result was considered to be stable (no change).…”
Section: Study Objective 1: Changes In Auditory Performancementioning
confidence: 99%
“…Nonetheless, long-term deafness negatively affects post-CI speech perception. Arisi et al [14] reported that CI significantly delayed deafness in poor performing adolescents with prelingual deafness. In our study, long-term deafness was similarly distributed between both groups, and thus was not a significant limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is likely explained by the postlingual group's late onset or progressive nature of hearing loss and thus accounts for the development of speech and language skills prior to CI. Similarly, the early age at implantation among the prelingual children reflects the well‐defined effectiveness of CI in this patient population 2–6. Delaying implantation among a group of prelingual children might be considered unethical in some instances.…”
Section: Discussionmentioning
confidence: 99%
“…3 Conversely, although earlier studies showed that delayed implantation in prelingual adolescents and adults resulted in limited improvements in speech perception skills, more recent works suggest that modest benefits are possible even in this population. [4][5][6][7] Nonetheless, hearing and language outcomes appear to be inversely correlated to age at implantation among prelingual children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation